Allozyme analysis of genetic diversity, genetic structure and interspecific relationship in genus Eriobotrya - Cai L.H.; Deng X.X.; Zhang W.C.; Huang H.W. (First international symposium on loquat, 2003)
Levels of allozyme diversity were determined in Eriobotrya populations. 24 loci for 12 enzyme systems of 120 materials from 4 species and 1 variant species: E. japonica Lindl., E. prinoides Rehd. et Wils., E. serrata Vidal, E. dayaoshanensis Chen. and E. prinoides var. daduheensis H.Z. Zhang, were investigated using isoelectric focus in thin-layer polyacrylamide slab gel. Fifty nine alleles were detected at 24 loci of 12 enzyme systems from 14 populations of Eriobotrya with the largest number of five. 15 in 22 loci were significant or extremely significant. Average expected heterozigosity (He) and the portion of polymorphic loci (P) of 10 populations of E. japonica were 0.320 and 69.6 respectively. Fixed indexes of the populations imply more heterozygous genotypes than the expected value of Hardy-Weinberg.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)